Enhanced high-rate performance of Zr-doped P2-Na0.67Ni0.33Mn0.67O2 cathode for sodium-ion batteries - Ananya Kumar; Sreeraj Puravankara (Next Energy)
Layered P2-type oxide compounds are an essential class of cathode materials for Na-ion batteries because of their superior capacity, average working potential, enhanced diffusivity of Na+ ions, and air stability compared to the O3-type oxides. Among the P2-type oxides, Na0.67Ni0.33Mn0.67O2 (NNMO) is one of the most explored materials because of its superior electrochemical performance. The inherent problem of low capacity retention because of phase changes during high-voltage cycling and Na+/vacancy ordering is still a considerable challenge for P2-type oxide cathodes. In this work, we have doped NNMO with Zr4+ ions at the Ni site to improve the compound's cycle stability. Partial substitution of Ni2+ ions with Zr4+ breaks the Na+/vacancy ordering and increases the interslab distance in the lattice, allowing easy movement of Na+ ions. These effects boost the cycle stability and the rate kinetics at higher rates. Herein, we report Na0.67Ni0.29Zr0.02Mn0.67O2, which delivers 80 mAh g−1 at 1 C rate and retains 90.1% of it after 500 cycles. At 5 C, it delivers 62 mAh g−1 after 700 cycles, showing an outstanding retention of 75.6%. Interestingly, a full cell made with commercial hard carbon anode delivers 74 mAh g−1 in the initial cycle and retains 65.7% after 50 cycles at 1 C, demonstrating an energy density of 229 Wh kg−1.